Enhancing Educational Evaluation by Incorporating Side Effects - Schrag, Francis (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
COVID-19 reveals the way single causes have multiple effects on children. Proponents of evidence-based education, like their colleagues in medicine, need to attend to the inevitable side effects produced by programs and policies. I explain why continuing motivation to learn is one outcome that no responsible evaluation should omit.